A voz da raça: uma expressão negra no Brasil que queria ser branco - Silva, Maria Aparecida Pinto (2003)
This paper addresses the interpretive analysis of the A Voz da Raça newspaper, and its conception as an expression of specific social group, the members of Frente Negra Brasileira. Analysis of the newspaper necessites putting its existence from 1933 —1937 into context. This paper looks at Getúlio Vargas Period and the transformation that occurred in the country since 1930. Still within than national country context I bring the debate about Race and Nation, pertinent to that historic moment, and which dialogue had its echoes in the articles of black newspaper. Analysis of the paper also necessites highlighting and understanting the internacional conection of the brazilian with north-americans and africans, trought the movement call Pan-africanism. Lastly, I analyse the newspaper articles' reflecion of systematic and reoccurring themes, such as the education of the black people self-esteem, advancement of the race and his hystorical role, among others, and also the black moviment trajectory, including the history of Frente Negra Brasileira.